Japanese family physicians' attitudes, difficulties, and perceived significance in managing mental health problems: A qualitative study - Natsuki Kajikawa; Shoji Yokoya; Sachiko Ozone (Journal of General and Family Medicine)
Abstract Background Family physicians (FPs) are expected to identify, diagnose, and treat mental health problems. Despite challenges such as limited time and low confidence in their skill as mental health providers, FPs generally consider mental health as a meaningful part of their profession. However, the role of the FP in mental health services is not clearly established in Japan. Studies have not been performed in countries without an established role of FPs' in mental health care. This study investigated Japanese FP's attitudes, difficulties, and perceived significance in managing mental health problems. Methods Semi‐structured interviews were conducted between September 2022 and February 2023. Participants were Japanese FPs involved in mental health care. Interview transcripts were subjected to thematic analysis. Results Thirteen FPs were interviewed. The FPs approached mental health problems “as a FP who provides holistic and comprehensive care” and “practice based on experience and self‐reflection.” The difficulties faced by FPs included “time management problems” and “referral management problems and conflicts.” Regarding significance, FPs mentioned that “gaining a deeper understanding of humanity” is important for managing mental health problems. Conclusions The attitude of Japanese FPs toward mental health care was based on awareness of the FP's specialty. Despite difficulties such as time and referral management issues, managing mental health problems was generally considered rewarding for professional growth.